Decoding IL-1 receptor 1 and 2 expression profiles across organs in sepsis - Tan, Chuyi; Wang, Weiqin; Ma, Han; Chen, Huan; Zhang, Huali; Peng, Yue; Yang, Yiying (Frontiers in Cell and Developmental Biology, 2025)
IntroductionInterleukin-1 (IL-1), a key inflammatory mediator, plays a critical role in the pathogenesis of sepsis. IL-1 signals through two major receptors, the signaling receptor IL-1R1 and the decoy receptor IL-1R2. However, the cell-type-specific and organ-specific expression dynamics of these receptors during sepsis remain poorly characterized.MethodsUsing publicly available single-cell RNA sequencing (scRNA-seq) datasets and flow cytometry validation, we systematically analyzed the expression profiles of IL-1R1 and IL-1R2 across multiple organs—including the lung, liver, heart, and small intestine in murine models of cecal ligation and puncture (CLP)-induced sepsis.ResultsWe found that IL-1R1 was predominantly expressed on non-immune cells (lung fibroblasts, liver endothelial cells and heart fibroblasts), and showed increased changes during sepsis. In contrast, IL-1R2 was primarily expressed on neutrophils and monocyte-derived macrophages in healthy conditions, with minimal expression on tissue resident macrophages such as alveolar macrophages and Kupffer cells). Sepsis induced a significant upregulation of IL-1R2 on neutrophils and monocyte-derived macrophages across all organs. However, resident macrophages in the lung, liver and heart maintain low expression during sepsis.DiscussionWe reveal distinct and compartmentalized expression landscapes for IL-1R1 and IL-1R2 across organs during sepsis. These findings offer a deep understanding of IL-1 receptors biology and shed light on their contributions to immune modulation and tissue-specific responses in sepsis.